Solubility and solubility modeling of polycyclic aromatic hydrocarbons in subcritical ethanol and water mixtures - Teoh, W.; Vieira De Melo, S.; Mammucari, R.; Foster, Neil (American Chemical Society, 2014)
The solubilities of anthracene and p-terphenyl in subcritical ethanol and water mixtures were measured using a static analytical equilibrium method between 393 and 473 K and at 50 and 150 bar. Temperature and ethanol composition in the subcritical solvent mixtures were found to have significant effects on the solubility of polycyclic aromatic hydrocarbons (PAHs). The effect of pressure on solubility is negligible when the range of pressure considered is relatively small. An empirical model was proposed in the present study to correlate the solubility of PAHs to temperature and ethanol mole fraction. UNIQUAC, O-UNIFAC, and M-UNIFAC models were compared, with the UNIQUAC model found to be in good agreement with experimental data. © 2014 American Chemical Society.